Experiences of Mothers with High-Risk Pregnancy - Dinar Indriani; Anisa Hasanah; Novi Irmala; Santi Susanti; Rai Nurani; Dyana Eka Fuzi Yulianti; Ida Maryati; Yanny Trisyani W (Britain International for Academic Research (BIAR) Publisher, 2026)
High-risk pregnancy is a major global health issue, marked by high maternal and infant mortality rates, and poses both physical and psychological challenges for women. This study aimed to explore the experiences of women with high-risk pregnancies through a scoping and literature review using Medline, PubMed, and Scopus. The search utilized keywords related to maternal experiences in high-risk pregnancies and included qualitative and mixed-method studies published in English from 2016 to 2024. A total of 15 articles were reviewed, revealing six key experiences: continuous care, communication, psychological support, non-pharmacological therapies, understanding of risks, and technological advancements. Findings indicate that social support, ongoing healthcare access, and health technologies can reduce anxiety and improve well-being. Effective communication, continuous care models, and telemonitoring during the pandemic have shown positive impacts on managing high-risk pregnancies.